THE ROLE OF GAMES IN TEACHING ENGLISH TO YOUNG LEARNERS - Inadullayeva Ruxsora; Maxmanazarova Feruza (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This study explores the role of teaching in English to young learners and highlights their impact on language ascquisition. In recent years, there has been growing interest in interactive and student-centered approaches, particularly in early language education. Games are considered an effective pedagogical tool as they create a motivating and low-anxiety learning environment.